Caring for the Hearts and Souls of Young Children: Acknowledging Spiritual Intelligence. Issue 1 (2nd January 2022) - Harris, Kathleen I.
Abstract : Cultivating young children's immense capacity for curiosity and wonder and helping them understand the connectedness of the world supports their growth as giving and empathic individuals.